MEMÓRIA E RESSIGNIFICAÇÃO DA HISTÓRIA EM LUEJI, O NASCIMENTO DE UM IMPÉRIO: interlocução entre tradição e memória na Angola de Pepetela. - MESQUITA, Fábio Henrique Novais de (2018)
From the main theories on memory, this research invests in an analysis of the Angolan literature written in Portuguese language from the novel Lueji, o nascimento de um império (1989), by Pepetela, the most expressive writer of this country's prose romanesque. This work appears as one of his most important creations for seeking the roots of a pre-colonial Angolanity to challenge the imposition of the European model to the detriment of the local culture. In addition, it reveals the great tension between tradition and modernity in a constant dialogue in the two space-times, in which Queen Lueji and ballerina Lu discuss with their contemporaries the validity of the ancestral traditions for their present. It is therefore important to understand memory as an agent of re-signification of the past, from the impressions of the present. Among these authors, Maurice Halbwachs (2003), Michel Pollak (1989), Joel Candau (2016) and Paul Ricouer (1994; 2007) recognize the possibility of reorganizing the world lived by people still in contact with the social networks in which memory is formed. However, in order for us to understand this lived world of the Angolan, we must understand how it relates to its territorial and subjective space, so the Humanist Cultural Geography, GHC, offers us with authors such as Eric Dardel (2011), Yi -Fu Tuan (2013), whose research recognizes the phenomenological experience as fundamental for the perception of space and place as categories humanized by the subjective action of the individuals who inhabit and build the lived world. For this, it is necessary that the Angolan subject feels like agent of its history and no longer object of study. Narrating and being the subject of the story itself are part of an afrocentric proposal coined by Molefi Kete Asante (2009), José P. Castiano (2010) and Innocence Mata (2012, 2014), who seek in African references such as Hampaté-Bâ 2010) and Vansina (2010), for a perspective in which the values and knowledge of the South are also possibilities of analysis of reality, as proposed by Boaventura Santos. To speak about tradition in Africa is to speak of an oralized knowledge transmitted from generation to generation, the griot being its main vehicle. It has the same function that the troubadour exerted in the medieval literature and its activity is transposed to the written narrative and assumed by the narrators of the plot. Therefore, we will also study the specificity of the narrative focus which, in Pepetelian writing, is configured differently. It is important to note that, by giving voice to different narrators, shifting the central narrator's point of view to various narrative perspectives, Pepetela questions the position of positivist historiography with its claim to truth unique to facts. Thus, Lídia Chiappini (1985) and Maria Lúcia Dal Farra (1978) will help us understand the position of subjects who intend to narrate the facts they have experienced or heard about. As a result, we have a hybrid literature, where writing and orality form a new pair that manifests itself at different levels, according to each author.